Array comparative genomic hybridization to characterize copy number variation in the human genome - Carter, Nigel (Henry Stewart Talks, 2009)
Array Comparative Hybridization (array-CGH) and measurement of copy number, Development of array-CGH technology from convention CGH on metaphase chromosomes, Initial use for identifying copy number changes in tumors, Identification of normal copy number variation, Increasing resolution of array-CGH reveals the scope, complexity and importance of normal copy number variation